Fruit and seed development in Hevea (clone RRIM 600) in Malaysia - Mohamad Husin, Sakhibun; Chin, H. F.; Hor, Y. L. (Rubber Research Institute of Malaysia, 1981)
Observation of the flowering habit, fruit set and seed development of Hevea brasiliensis Muell Arg. was carried out on clone RRIM 600. Flowering appeared to be more frequent under exposed, sparsely planted conditions and on flat + terrain. Morphological and structural changes continued from fruit set until dehiscence. The fruits ripened and dehisced from twenty-three to twenty-four weeks after flowering. Seed viability was highest before fruit dehiscence. At this stage the dry + weights of the fruit and the seed were highest and their moisture content was lowest